Rethinking the Federal Role in State Criminal Justice - Hoffmann, Joseph L. (2009)
This Essay argues that federal habeas review of state criminal cases squanders resources the federal government should be using to help states reform their systems of defense representation. A 2007 empirical study reveals that federal habeas review is inaccessible to most state prisoners convicted of non-capital crimes, and offers no realistic hope of relief for those who reach federal court. As a means of correcting or deterring constitutional error in non-capital cases, habeas is failing and cannot be fixed. Drawing upon these findings as well as the Supreme Court's most recent decision applying the Suspension Clause, the authors propose that Congress eliminate federal habeas review of state criminal judgments, except for cases including certain claims of actual innocence, retroactively applicable rules, or the sentence of death. The federal government should leave the review of all other state criminal judgments to the state courts and invest, instead, in a new federal initiative to encourage improved state defense services, an approach that can deter and correct constitutional error more effectively than any amount of habeas litigation ever could